Determinasi Manajemen Laba oleh Kompetensi SDM, Literasi Digital, dan Keyakinan Finansial Pada Gen Z - Mauliddia, Isqi; Apriliana, Depinkkan; Kristianto, Giovanny Bangun (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat 2025, 2025)
Generation Z, as digital natives, plays a crucial role in the digital economy, not only as students and young employees but also as micro and small entrepreneurs. In this context, the issue of earnings management is no longer confined to large corporations but has become relevant at the individual and micro-business level. This study analyzes the influence of human resource (HR) competence, digital literacy, and financial self-efficacy on the tendency to engage in earnings management among Generation Z in Banyumas Regency. A quantitative explanatory method was employed using primary data collected from 120 respondents aged 18–27 years through questionnaires. Multiple linear regression analysis with SPSS revealed that HR competence, digital literacy, and financial self-efficacy significantly affect the tendency toward earnings management, both partially and simultaneously, with a coefficient of determination (R²) of 0.482. The findings highlight HR competence as the most dominant factor, while digital literacy and financial self-efficacy also contribute, albeit with smaller effects. This study concludes that earnings management among Generation Z is shaped not only by personal factors but also by external influences such as social norms, organizational culture, and regulatory oversight. The study contributes to behavioral accounting and finance literature and offers practical implications for policymakers, universities, and financial institutions to foster competence, digital literacy, and financial ethics among young generations